1993
DOI: 10.1287/mnsc.39.8.937
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Attribute Ranges on Weights in Multiattribute Utility Measurements

Abstract: Multiattribute utility theory requires a specific relation between the range of outcomes of each attribute and the weight for that attribute. The greater the range, the greater the weight has to be. Experimental results show that subjects do not adjust their judgments properly if the range is varied. For the two methods tested the adjustment is smaller than required by theory. The bias was smaller for a regression procedure than for the direct ratio method. Weights based on an intuitive range were not found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(82 citation statements)
references
References 11 publications
3
79
0
Order By: Relevance
“…In SMART (von Winterfeldt and Edwards, 1986), ratio (Edwards, 1977) and point allocation methods the decision maker directly assigns weights to objectives. These methods do not explicitly incorporate ranges when weight judgments are derived (von Nitzsch andBorcherding, 1993). In AHP pairwise comparisons typically do not include the impact ranges.…”
Section: Multi-criteria Decision Analysis (Mcda)mentioning
confidence: 99%
See 1 more Smart Citation
“…In SMART (von Winterfeldt and Edwards, 1986), ratio (Edwards, 1977) and point allocation methods the decision maker directly assigns weights to objectives. These methods do not explicitly incorporate ranges when weight judgments are derived (von Nitzsch andBorcherding, 1993). In AHP pairwise comparisons typically do not include the impact ranges.…”
Section: Multi-criteria Decision Analysis (Mcda)mentioning
confidence: 99%
“…The range insensitivity bias refers to the phenomenon that participants do not sufficiently adjust their weights if the range of attributes is changed (von Nitzsch and Weber, 1993). For instance, if the difference between the lowest and highest costs increases from 100,000 € to 500,000 € after the addition of a new alternative and all other ranges remain the same, then the weight of the cost objective should increase.…”
Section: Biases Related To Weighting Proceduresmentioning
confidence: 99%
“…Borcherding et al (1991) reported that in their experiment decision makers found it difficult to give consistent TRADEOFF statements. Regardless of this, TRADEOFF weights have been used to validate the weights derived with other methods (von Nitzsch and Weber, 1993). We think that the dependency between inconsistencies of the statements and the number of attributes compared simultaneously needs further attention (Hypothesis 6, Exhibit 1).…”
Section: H6mentioning
confidence: 99%
“…Contrary to this prediction, several studies have provided evidence that weight increases with increase in range (Fischer, 1995;Goldstein, 1990;von Nitzsch & Weber, 1993). In these studies the researchers have observed this relationship while using a variety of different methods (direct importance ratings, swing weights, regression weights, or weights inferred from value judgments).…”
mentioning
confidence: 93%